Multifunctional fluorescent probe for simultaneous revealing Cys and ONOO– dynamic correlation in the ferroptosis - Liu, Xiongbo (Elsevier, 2025)
Ferroptosis is a type of lipid peroxidation-induced apoptosis brought on by imbalances in iron metabolism and redox. It involves both the thiol-associated anti-ferroptosis pathway and the excessive buildup of reactive oxygen species (ROS), which stimulates the ferroptosis pathway. Determining the precise control mechanism of ferroptosis requires examining the dynamic connection between reactive sulfur species (RSS) and ROS. Cysteine (Cys) and peroxynitrite (ONOO–) are highly active redox species in organisms and play dynamic roles in the ferroptosis process. In this study, a coumarin dye was conjugated with specific response sites for Cys and ONOO–, enabling the simultaneous detection of Cys and ONOO– through the green and red fluorescence channels, respectively (λem = 498 nm for Cys and λem = 565 nm for ONOO–). Using the probe LXB, we monitored the changes in Cys and ONOO– levels in the ferroptosis pathway induced by erastin. The results demonstrate a significant generation of ONOO– and a noticeable decrease in intracellular Cys levels at the beginning upon erastin treatment and finally maintains a relatively low level. This study presents the first probe to investigate the intracellular redox modulation and control between Cys and ONOO– during ferroptosis, providing valuable insights into the potential mutual correlation between Cys and ONOO– in this process.